Developmental role of the tomato Mediator complex subunit MED18 in pollen ontogeny. (12th August 2018) - Pérez‐Martín, Fernando; Yuste‐Lisbona, Fernando J.; Pineda, Benito; García‐Sogo, Begoña; Olmo, Iván del; de Dios Alché, Juan; Egea, Isabel; Flores, Francisco B.; Piñeiro, Manuel; Jarillo, José A.; Angosto, Trinidad; Capel, Juan; et al.
Summary: Pollen development is a crucial step in higher plants, which not only makes possible plant fertilization and seed formation, but also determines fruit quality and yield in crop species. Here, we reported a tomato T‐DNA mutant, pollen deficient1 ( pod1 ), characterized by an abnormal anther development and the lack of viable pollen formation, which led to the production of parthenocarpic fruits. Genomic analyses and the characterization of silencing lines proved that pod1 mutant phenotype relies on the tomato SlMED18 gene encoding the subunit 18 of Mediator multi‐protein complex involved in RNA polymerase II transcription machinery. The loss of SlMED18 function delayed tapetum degeneration, which resulted in deficient microspore development and scarce production of viable pollen. A detailed histological characterization of anther development proved that changes during microgametogenesis and a significant delay in tapetum degeneration are associated with a high proportion of degenerated cells and, hence, should be responsible for the low production of functional pollen grains. Expression of pollen marker genes indicated that SlMED18 is essential for the proper transcription of a subset of genes specifically required to pollen formation and fruit development, revealing a key role of SlMED18 in male gametogenesis of tomato. Additionally, SlMED18 is able to rescue developmental abnormalities of the Arabidopsis med18 mutant, indicating that most biological functions have been conserved in both species. Significance Statement: Pollination is a key development process in the life cycle of flowering plants. Genetic and molecular characterization of a tomato mutant have led to the identification of POD1 gene encoding the Mediator complex subunit MED18 whose function is required for tapetum tissue degeneration, a crucial step for pollen development. Furthermore, we show that MED18 fulfils an essential role in tomato, ensuring proper gene regulation during pollen ontogeny.